Dynein achieves processive motion using both stochastic and coordinated stepping - Qiu, Weihong (2012)
Processivity, the ability of single molecules to move continuously along a track, is a fundamental requirement of cargo-transporting molecular motors. Here, we investigate how cytoplasmic dynein, a homodimeric, microtubule-based motor, achieves processive motion. To do this we developed a versatile method for assembling Saccharomyces cerevisiae dynein heterodimers using complementary DNA oligonucleotides covalently linked to dynein monomers labeled with different organic fluorophores. Using two-color, single-molecule microscopy and high-precision, two-dimensional tracking, we find dynein has a highly variable stepping pattern that is distinct from all other processive cytoskeletal motors, which use “hand-over-hand” mechanisms. Uniquely, dynein stepping is stochastic when its two motor domains are close together. However, coordination emerges as the distance between motor domains increases, implying a tension-based mechanism governs these steps. This plasticity may allow tuning of dynein for the diversity of cellular functions it performs.